In-vitro inhibitory activities of potential probiotic isolated from pangasius nasutus against aeromonas hydrophila and streptococcus agalactiae - Shafiq Johar,; Puvaneswari Puvanasundram,; De Cruz, Clement Roy; Chou, Min Chong; Md Yasin Ina-Salwany,; Keng, Chin Lim; Noordiyana Mat Noordin,; Murni Karim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In aquaculture, using probiotics is crucial for strengthening the immune system and encouraging the growth and survival of many aquatic organisms, including the Pangasius species. This approach is particularly significant given the impact of bacterial diseases on Pangasius survival. This study aimed to assess the effectiveness of probiotics isolated from Pangasius nasutus as alternatives to antibiotics for combating infections caused by Aeromonas hydrophila and Streptococcus agalactiae. Potential bacteria were isolated from the intestine and stomach of healthy P. nasutus. Seventy probiotic strains were successfully isolated and further screened using A. hydrophila and S. agalactiae as pathogens in an in vitro disc diffusion assay. Preliminary screenings indicated that five probiotic strains inhibited the growth of A. hydrophila. Stomach-derived strain S1 and intestine-derived strain L1 suppressed A. hydrophila growth with inhibition zones of 10.5±1 mm and 8.5±1 mm, respectively. Likewise, strains L2, L8, and L12 from the intestine showed inhibitory zones of 6.0±1 mm, 6.5±1 mm, and 6.0±1 mm, respectively. Of these, only L12 inhibited the growth of S. agalactiae with a clear zone of 5.0±1 mm. In the elimination of pathogenic strains, potential strains S1 and L1 did not grow on the Aeromonas isolation medium. Co-culture assays demonstrated that both potential strains significantly inhibited Aeromonas hydrophila growth at concentrations of 106 and 108 CFU mL-1 over 48- and 96-hour periods, respectively. The potential bacterial strains were identified using 16s rRNA gene sequencing and were classified as follows: S1 - Lactococcus lactis, L1 - Weissella confusa, L2 - Cosenzaea myxofaciens, L8 - Lactococcus garvieae, and L12 - Plesiomonas shigelloides. Strain S1 L. lactis and strain L1 W. confusa are suggested for further evaluation and acquired additional research to fully elucidate their mechanisms and potential as probiotics.